The cause factors of the fisherman's poverty village in Tanjung Baru sub district in Tanah Merah of Indragiri Hilir regency - Candra, Riski; Ekwarso, Hendro; ', Eriyati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research has been done village in Tanjung Baru Sub district in TanahMerah of Indragiri Hilir regency by many considerations that there are still many fishermen in poverty. This research aim is to know the cause factors of the fisherman’s poverty in Desa Tanjung and how about the percentage of the fishermen’s income from their job as a fisherman to their family’s responsible and their necessity.The sample was taken village in Tanjung Baru Sub district in Tanah Merah of Indragiri Hilir regency by using random sampling method. The analysis method was descriptive quantitative.The population in this research is the poor fisherman village in Tanjung Baru Sub district in Tanah Merah of Indragiri Hilir regency with the total is 96 fishermen and the population in this research is the sample by the Slovin’s formulation. The data analysis is descriptive analysis by analyzing result data in order to be the background’s problem, also calculated by quantitative after that compare by the theory and make the conclusion.Based on the result analyzing that ahs been done, the fisherman’s poverty showed that income, education, assets, skill, commercial life style and the family’s member who 3 up to 6 members as generally very significantly influencing to the fisherman’s poverty.Keywords: fisherman’s poverty, fisherman’s income.